Concerns on healthcare access, utilization, and safety due to COVID-19 among American adults with vision loss. Issue 3 (July 2022) - Nagarajan, Niranjani; Varadaraj, Varshini; Chanes-Mora, Paola; Rosenblum, L. Penny; Swenor, Bonnielin K.
Abstract: Background: Limited studies have indicated that Americans with vision loss are differentially impacted by COVID-19. Objective: We examined concerns with healthcare and safety among Americans with vision loss during the early phase of the pandemic (April 2020). Methods: The Flatten Inaccessibility Survey assessed the impact of COVID-19 on healthcare (pharmacy access, maintenance of eyecare regimen, caregiver access, and resource denial) and safety (social distancing, clean surfaces, and touching public signage) concerns among Americans with low vision or who were blind. Multivariable logistic regression was used to determine associations between respondent characteristics and each concern. Results: A total of 1921 adults responded to the survey, of whom 65% were blind and 35% had low vision. Most respondents were female (63%) and white (74%). Respondents with additional disabilities/comorbidities were more likely to report healthcare access concerns (pharmacy access, eyecare regimen, caregiver access, and ventilator access) and safety concerns (social distance, clean surfaces, and touching signage) than those with vision loss alone. In addition, females, those identifying as "other" gender, older individuals, and people with adult onset of vision impairment were more likely to experience COVID-19–related concerns and challenges related to healthcare and overall safety. Conclusion: These results suggest that while Americans with vision loss have been differentially impacted by COVID-19, adults with vision loss and additional disabilities/comorbidities are more likely to have concerns with healthcare and safety than those with vision loss alone.